The effects of hesperidin on idiopathic pulmonary fibrosis evaluated by histopathologial-biochemical and micro-computed tomography examinations in a bleomycin-rat model. - Gormeli, Cemile Ayse; Sarac, Kaya; Ciftci, Osman; Timurkaan, Necati; Malkoc, Siddik (Allied Acad, 2016)
Idiopathic Pulmonary Fibrosis (IPF) is a chronic, progressive parenchymal lung disease. The pathology is characterized by recurrent injury to microscopic alveolar epithelial cells. These injuries activate inflammatory cells, resulting in the proliferation of fibroblasts and alveolar tissue damage. Interstitial inflammation, advanced oxidative stress, and abnormal antioxidant activity were demonstrated to be the main causes of IPF. Hesperidin (HP) is a bioflavonoid with anti-inflammatory, antioxidant, anticarcinogenic, and analgesic actions. HP may be able to prevent pulmonary fibrosis, and may ultimately lead to healthy lung function. We hypothesized that HP could prevent Bleomycin (BLC)-induced pulmonary fibrosis due to its biochemical, antioxidant, and anti-inflammatory properties and may ultimately lead to healthy lung function. Based on these findings, we hypothesized that HP could prevent BLC-induced pulmonary fibrosis due to its biochemical, antioxidant, and anti-inflammatory properties. The animals were divided into 4 groups with 14 rats per group. The experimental treatments were as follows: Control, BLC, HP, and BLC+HP. Six of the 14 lungs in each group were sent for micro CT analysis. The remaining 8 lung specimens were harvested for histopathological and biochemical analyses. BLC-treated rats showed marked histopathological changes in the lungs. In these rats, thickening of interalveolar septa due to macrophage and lymphocyte infiltration, as well as fibroblast proliferation, were observed. Histopathological changes were less severe in the BLC+HP group compared with the BLC group. HP treatment led to a decrease in lipid peroxidation and an increase in antioxidant status compared with the BLC group. Also micro-CT showed a significant positive correlation with histopathological and biochemical results. To the best of our knowledge, this is the first study to evaluate the beneficial effects of HP against pulmonary fibrosis using histopathological, biochemical, and micro-CT analyses and HP successfully minimized the severity of BLC-induced lung injury, which was used as a model for IPF.
Keywords: Idiopathic pulmonary fibrosis; Micro-computed tomography; Hesperidin